Legal Innovation in Environmental Policy: Lessons from the U.S. Climate Experience in Comparison with Central Asia (Zien Journal of Social Sciences and Humanities, 2025)
Climate change is not only an environmental issue—it is a legal one. Around the world, governments are reshaping legal systems to respond to complex climate challenges. This article explores how legal innovation in the United States has developed in response to climate change, with a particular focus on public participation, decentralization, and resilience planning. Drawing from the perspective of an international law student, it compares the U.S. model with legal approaches emerging in Central Asia, including Kazakhstan, Uzbekistan, and Kyrgyzstan. While Central Asian states have made substantial progress in national climate commitments, they often rely on centralized frameworks and administrative planning, with limited space for legal experimentation or public engagement. The article does not seek to critique either system but offers reflections on how future legal frameworks—particularly in rapidly developing regions—may benefit from blending structure with flexibility, and ambition with local empowerment.